Analisis sub sektor perkebunan Provinsi Jambi - Popi Fitriandi; Hardiani Hardiani; Candra Mustika (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2019)
The purpose of this research is first, to know and analyze the development of the land area, labor, and GRDP of the plantation sub-sector in Jambi Province. Second, knowing and analyzing the contribution of the plantation sub-sector to the agricultural sector and the GRDP of Jambi Province. Third, to analyze the effect of land area and labor on the output of the plantation sub-sector in Jambi Province. The development of the land area, labor, GDP in the plantation sub-sector of Jambi Province for the period 2000-2015 continued to increase, with an average increase in land area of ​​2.52%, a workforce of 2.74%, GRDP of the plantation sub-sector by 7.84%. The contribution of the plantation sub-sector to the agricultural sector and the GRDP of Jambi Province for the period 2000-2015 also continued to increase. Based on the results of multiple linear regression calculations, simultaneously land area and labor have a significant effect on the output of the plantation sub-sector in Jambi Province. Partially, land area has a significant effect on the output of the plantation sub-sector in Jambi Province, while labor does not affect the output of the plantation sub-sector in Jambi Province. Keywords: Land area, Labor, Gross regional domestic product of plantation sub sector